PENERAPAN PRODUK SHELTER PEJALAN KAKI ANAK DI SLB KREASI MANDIRI - Febriane Paulina Makalew; Steve Wilben Maqcuarie Supit (Jurnal Abdi Insani, 2022)
The development of research results related to children's pedestrian shelters is implemented in the form of product applications at partner locations of Kreasi Mandiri Special Schools (SLB). The materials developed for the construction of the shelter are composite materials and coconut wood. School areas that are used by students and children visiting schools need outdoor shelters that are safe, comfortable and prioritize children's activities. The Kreasi Mandiri SLB school area in Winangun Atas village does not yet have adequate children's pedestrian shelters. The purpose of this activity is to explain the stages of implementing pedestrian shelter products and explain the changes that have occurred due to the implementation of research results at the Kreasi Mandiri SLB school as a service location. The method used is the construction of shelters based on research results of shelter design and construction. The manufacture of shelter products is carried out by providing materials according to design guidelines and carried out by expert workers, the implementation team of the Manado State Polytechnic. The result obtained is the availability of pedestrian shelters. Making this shelter consists of the stages of preparatory work, construction of shelter construction, painting work and arrangement of the area around the shelter. The shelter is used by school residents and visitors as an outdoor activity facility for students and school teachers. The application of research results is carried out and utilized directly by service partners. Continuation of the application of research results into an evaluation of the use of the shelter to improve its quality. This Vocational Innovation Product Business Implementation (PUPIV) activity is the basis for the school to continue the school environment development program and other environmentally friendly products. The application of research results to the community in the form of shelters becomes optimal with the involvement of implementers and partners. The use of shelters provides evaluation results for optimal use of facilities.